The global burden of tuberculosis mortality in children: a mathematical modelling study - Dr Peter J Dodd, PhD; Courtney M Yuen, PhD; Charalambos Sismanidis, PhD; James A Seddon, PhD; Helen E Jenkins, PhD (Elsevier, 2017)
Background: Tuberculosis in children is increasingly recognised as an important component of the global tuberculosis burden, with an estimated 1 million cases in 2015. Although younger children are vulnerable to severe forms of tuberculosis disease, no age-disaggregated estimates of paediatric tuberculosis mortality exist, and tuberculosis has never been included in official estimates of under-5 child mortality. We aimed to produce a global mortality burden estimate in children using a complementary approach not dependent on vital registration data. Methods: In this mathematical modelling study, we estimated deaths in children younger than 5 years and those aged 5-14 years for 217 countries and territories using a case-fatality-based approach. We used paediatric tuberculosis notification data and HIV and antiretroviral treatment estimates to disaggregate the WHO paediatric tuberculosis incidence estimates by age, HIV, and treatment status. We then applied systematic review evidence on corresponding case-fatality ratios. Findings: We estimated that 239 000 (95% uncertainty interval [UI] 194 000-298 000) children younger than 15 years died from tuberculosis worldwide in 2015; 80% (191 000, 95% UI 132 000-257 000) of these deaths were in children younger than 5 years. More than 70% (182 000, 140 000-239 000) of deaths occurred in the WHO southeast Asia and Africa regions. We estimated that 39 000 (17%, 23 000-73 000) paediatric tuberculosis deaths worldwide were in children with HIV infections, with 31 000 (36%, 19 000-59 000) in the WHO Africa region. More than 96% (230 000, 185 000-289 000) of all tuberculosis deaths occurred in children not receiving tuberculosis treatment. Interpretation: Tuberculosis is a top ten cause of death in children worldwide and a key omission from previous analyses of under-5 mortality. Almost all these deaths occur in children not on tuberculosis treatment, implying substantial scope to reduce this burden. Funding: UNITAID, National Institutes of Health, and National Institute for Health Research.